PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENILAIAN PRESTASI PEGAWAI MENGGUNAKAN METODE SAW, AHP, DAN TOPSIS - Diki Hidayat; Aldiyansyah; Muhammad Adji Assalmi; Alfrianto Pratama Ginting; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Having the best talent is a very important aspect for companies, as good people and high competence can improve a company's productivity and performance, and can create great leaders in the future. PT. Bank Pembangunan Daerah Banten, Tbk. have the best staff to process candidate data, but due to the lack of standards and still using manual systems, the evaluation process is still not transparent, accurate, reliable, and takes a long time. increase. Determining the best employees at Bank banten requires a decision support system as a recommendation to the board of directors. A decision support system that uses three methods to determine the best employees who worked in this study: Simple Additive Weighting (SAW), Analytical Hierarchy Process (AHP), Ordering by Similarity to Ideal Solution (TOPSIS). This study evaluated the best Bank banten based on predetermined criteria such as individual performance ratings, work unit performance, attendance, behavior, goal attainment in employment, employee training, evaluation documents, presentations, and interview results. Create a decision support system that can recommend employees.